Avaliação de glaucoma em pacientes com a síndrome congênita do Zika vírus - Oliveira, Daniela Raposo Vieira De [UNIFESP] (2020)
Purpose: To perform an ophthalmologic evaluation, with emphasis on glaucoma diagnosis, in infants with congenital Zika syndrome. Patient and methods: This crosssectional study included 188 eyes of 107 children (1.1 ± 0.3 years [range, 0.3 – 1.8 years]) with congenital Zika syndrome. The confirmation of the syndrome was possible in 77/107 (72.0%) of the enrolled infants based on positive immunoglobulin M antibody capture enzyme-linked immunosorbent assay for Zika virus in the cerebrospinal fluid. All infants underwent a complete ophthalmic examination and bilateral fundus imaging was captured using a wide-angle digital fundus camera (RetCam™; Natus Medical Inc., Pleasanton, CA). Results: Five eyes (2.6%) presented two criteria for glaucoma diagnosis; one eye (0.5%) presented increased intraocular pressure and increased vertical cup-to-disc ratio; three eyes (1.6%) presented increased horizontal corneal diameter and increased vertical cup-to-disc ratio; and one eye (0.5%) myopia related to increased axial length and increased vertical cup-to-disc ratio. When excluding the cup-to-disc ratio criterion, there was no case that fulfilled the childhood glaucoma diagnosis criteria in this sample. A significant correlation was observed between increased vertical cup-to-disc ratio and small cephalic perimeter at birth (p=0.002) and presence of clinical macular lesions (p=0.031). Conclusion: Although childhood glaucoma was not detected in this sample, according to the established criteria, increased vertical cup-to-disc ratio is present in children with congenital Zika syndrome, associated with microcephaly and clinical macular lesions at birth. This finding may lead to a misdiagnosis of glaucoma.